(untitled) (Physical Education, Health and Social Sciences, 2025)
The goal of this study is to see how effective positive psychology treatments (PIs) are at preventing internet addiction and improving people’s relationship quality. The suggested hypothesis therefore proposes that “positive psychology intervention would reduce internet addiction, leading to better interpersonal relationships." For this reason, 40 students with Internet addiction and low interpersonal relationship were selected using a purposive convenient sampling technique for non-probability purposes. This study is based on quasi-experimental, pre-post quantitative design, for which nine sessions of PI-based treatment were conducted. Multidimensional Scale of Perceived Social Support (MSPSS) (Zimet et al., 1988) and Internet Addiction Test (Young, 2009) were the selected measures. According to the results, PI is an effective method for treating Internet Addiction and hence there is significant change in the pretest and posttest value (p<0.05) in reducing Internet use (P = 0.01) and improving the quality of Interpersonal relationships (p= 0.01). For data analysis, SPSS version 22 was used. The findings of the present study provide evidence that positive psychology interventions are relevant with the culture of Pakistan and reflect on the needs of young adults.